Diagnosis and Management of Vesicouterine Fistula (Youssef’s Syndrome): A Case Report - Amir Fauzi; Ratih Krisna; Hadrians Kesuma Putra; Sonia Prima Arisa Putri; Febi Stevi Aryani; Hana Andrina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Vesicouterine fistula (VUF) is a rare pathological communication between the uterus or cervix and the bladder. Youssef's syndrome is an atypical presentation of a patient with a vesicouterine fistula, characterized by a triad of cyclic hematuria, amenorrhea, and absence of urinary incontinence. Because of this atypical presentation, the patient may go undiagnosed and patient management will be delayed. Case presentation. A 39-year-old woman complained of hematuria. The patient underwent a second caesarean section in 2008 and a few weeks after the procedure the patient complained of leakage of urine from her vagina. Six months later the patient complained hematuria on her menstrual cycle and amenorrhea, with absence of urinary incontinence. Ultrasound examination found adhesions between the uterus and vagina, and irregular bladder mucosa. Patient underwent cystoscopy with endometriosis were suspected on vesicovaginal repair scars and a bladder biopsy was also performed with the results of no endometrial stroma and glands then followed by hysteroscopy. Hysteroscopy result showed a 20 mm diameter hole with irregular margins. Subsequently, the patient was treated with hysterorrhaphy laparotomy and fistula repair. Conclusion. One type of vesicouterine fistula is Youssef's syndrome, which is a complication following a lower segment caesarean section with undiagnosed bladder injury. The diagnosis can be confirmed by cystoscopy, intravenous pyelography, hysterosalpingogram, sonography, and other types of imaging tests. Management of patients with VUF can be conservative, medical, or surgical.